Cultural Narratives: Yat R's Religious Expressions in Si Rawing on Radio Cakra Bandung - Hermawan, Ucep; Qomaruzzaman, Bambang; Darmawan, Dadang (Hanifiya: Jurnal Studi Agama-Agama, 2025)
The phenomenon of religious communication through online media, such as YouTube, has introduced new dimensions to religiosity, categorized as religion online and online religion. Religion online uses digital platforms as tools for disseminating religious messages and storing information, such as digital manuscripts and sermons, accessible anytime. In contrast, online religion creates a space for active religious communication and practices, especially prominent during the COVID-19 pandemic when religious activities shifted online. This study focuses on the online religion aspect by examining the spiritual experiences expressed by Sundanese cultural figure Kang Yat R through the Si Rawing storytelling series on YouTube. Employing a qualitative case study approach, data was collected through in-depth interviews with Kang Yat R and analysis of YouTube content. The results reveal that Si Rawing reflects Kang Yat R’s religious experiences in three dimensions: thought (doctrine), action (ritual), and community (group), in alignment with Joachim Wach's framework. This study underscores the role of online platforms in preserving and transmitting religious and cultural heritage to younger generations.